Penggunaan Aplikasi E-Learning "HATI” dalam Pembelajaran Bahasa Arab di Perguruan Tinggi Keagamaan Islam Negeri - Hamid, M Abdul; Ifawati, Nur Ila; Charis, M Abdullah; Qomari, Nur (Arabi : Journal of Arabic Studies, 2023)
Arabic learning at the State Islamic Religious Universities has not used many applications. This is due to the unavailability of the proper application. The Arabic learning application "HATI" can contribute to learning Arabic. The purpose of this study is to describe the use of the "HATI" application from the perspective of PTKIN students. The research method used is descriptive quantitative using a questionnaire instrument. This study's results indicate that using the HATI application in learning Arabic at PTKIN is very easy and interesting. This is proven that 26.25% of respondents answered that it was effortless to operate the HATI application, 42.43% of respondents answered that it was easy, 22.06% of respondents answered that it was not easy, and 8.97% of respondents said it was not very easy. While 37.87% of respondents answered very interesting, 48.16% answered interesting, 8.82% answered less attractive, and 4.96% answered very unattractive.